Tingkat Penggunaan Antibiotik dan Pola Peresepannya Pada Infeksi Saluran Pernapasan (ICD-10: J00-J99) di Indonesia Selama Pandemi COVID-19 - Misworo, Misworo; Kusuma, Ikhwan Yuda; Kurniasih, Khamdiyah Indah; Nurkholis, Fiqih; Fauziah , Fauziah (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Introduction: Respiratory tract infections (RTIs) contribute substantially to global antibiotic consumption, raising concerns about antimicrobial resistance (AMR). This study aimed to analyze antibiotic prescribing patterns for respiratory disorders in an Indonesian teaching hospital during the COVID-19 pandemic. Methods: This retrospective, cross-sectional study examined systemic antibiotic prescriptions based on the Anatomical Therapeutic Classification (ATC: J01) for respiratory diseases (ICD-10: J00-J99) at Cilacap Government Teaching Hospital between January and December 2021. Data were extracted from electronic medical records (e-MR), including patient demographics (i.e. age and sex), ICD codes and name of antibiotics. We analyzed WHO AWaRe classifications, administration routes, and seasonal patterns based on patient’s entry and antibiotic use. Results: The study included 2,395 patients with antibiotic prescriptions for respiratory disorders. The Watch group antibiotics accounted for 85.6% of prescriptions, with the highest use among adults (86.2%). Parenteral administration (71.5%) was more common than oral administration (28.5%). Pneumonia (38.2%) and chronic obstructive pulmonary disease (27%) were the most common indications. Antibiotic use peaked in December (n=529) and was lowest in July (n=84). Ceftriaxone (n=838), azithromycin (n=270), cefixime (n=262), levofloxacin (n=216), and meropenem (n=56) were among the top prescribed antibiotics. Conclusion: The study highlights the predominant use of broad-spectrum and parenteral antibiotics for respiratory disorders, raising concerns about AMR. Factors such as seasonality, disease patterns, and diagnostic challenges may have influenced prescribing practices. Implementing antimicrobial stewardship programs, promoting evidence-based guidelines, and addressing modifiable risk factors are crucial to combat AMR and optimize patient outcomes during and beyond the COVID-19 pandemic.